Counseling program for improving anxiety and depression in people with HIV at a community-based organization in Lima, Peru - García Maiz, Evelin (2024)
Objective. To demonstrate the effectiveness of the Counseling Program in improving anxietyand depression in people with HIV at a community-based organization in Lima, Peru. Methods. A quasi-experimental study with control and experimental groups was conducted, applying pre- and post-test measurements. The measurement instrument used was the Beck Anxiety andDepression Inventory, applied to a sample of 36 people living with HIV in a community-based organization. The Wilcoxon signed-rank test was used to test the hypotheses. Results. Theresults show no significant difference between the control and experimental groups regardingsexual orientation, age, educational level, and socioeconomic level (p > 0.05). Furthermore, the Counseling Program demonstrated a positive effect on levels of anxiety and depression (p < 0.01). Conclusions. The application of the Counseling Program was effective, as evidenced by the reduction in anxiety and depression levels in people with HIV.